Pembuatan Bibliografi Beranotasi Terbitan Bank Indonesia Khusus Kajian Ekonomi Regional Tahun 2010-2012 di Perpustakaan KPW BI Wilayah VIII - Pratiwi, Julia; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
In this paper, an annotated bibliography contains bank indonesia issue especially about regional economic studies in 2010-2012. Collected in region VIII BI KPw library. The aim of this study was to deseribe the bibliography arrange process. Data was collected through documentation study i.e. searching and reading documents that retrieved from the library information retrieval system tool. The result of documents reading activities was arranged in annotated bbliography. The arrange process can be summerized as : (a) extractly the title of bibliofraphy, (b) coding, (c) selecting of library material, (d) classifying, (e) making keywords, (f) arraning keywords index, (g) typing the bibliography, (h) verifying the the bibliography. Keywords: annotated, bibliography Â